Acute Ischemic Stroke Interventions in the United States and Racial, Socioeconomic, and Geographic Disparities. (7th December 2021) - de Havenon, Adam; Sheth, Kevin; Johnston, Karen C.; Delic, Alen; Stulberg, Eric; Majersik, Jennifer; Anadani, Mohammad; Yaghi, Shadi; Tirschwell, David; Ney, John
Abstract : Background and Objectives: In patients with ischemic stroke (IS), IV alteplase (tissue plasminogen activator [tPA]) and endovascular thrombectomy (EVT) reduce long-term disability, but their utilization has not been fully optimized. Prior research has also demonstrated disparities in the use of tPA and EVT specific to sex, race/ethnicity, socioeconomic status, and geographic location. We sought to determine the utilization of tPA and EVT in the United States from 2016–2018 and if disparities in utilization persist. Methods: This is a retrospective, longitudinal analysis of the 2016–2018 National Inpatient Sample. We included adult patients who had a primary discharge diagnosis of IS. The primary study outcomes were the proportions who received tPA or EVT. We fit a multivariate logistic regression model to our outcomes in the full cohort and also in the subset of patients who had an available baseline National Institutes of Health Stroke Scale (NIHSS) score. Results: The full cohort after weighting included 1, 439, 295 patients with IS. The proportion who received tPA increased from 8.8% in 2016 to 10.2% in 2018 ( p < 0.001) and who had EVT from 2.8% in 2016 to 4.9% in 2018 ( p < 0.001). Comparing Black to White patients, the odds ratio (OR) of receiving tPA was 0.82 (95% confidence interval [CI] 0.79–0.86) and for having EVT was 0.75 (95% CI 0.70–0.81). Comparing patients with a median income in their zip code of ⩽$37, 999 to >$64, 000, the OR of receiving tPA was 0.81 (95% CI 0.78–0.85) and for having EVT was 0.84 (95% CI 0.77–0.91). Comparing patients living in a rural area to a large metro area, the OR of receiving tPA was 0.48 (95% CI 0.44–0.52) and for having EVT was 0.92 (95% CI 0.81–1.05). These associations were largely maintained after adjustment for NIHSS, although the effect size changed for many of them. Contrary to prior reports with older datasets, sex was not consistently associated with tPA or EVT. Discussion: Utilization of tPA and EVT for IS in the United States increased from 2016 to 2018. There are racial, socioeconomic, and geographic disparities in the accessibility of tPA and EVT for patients with IS, with important public health implications that require further study.